The Influence of Experiential Marketing and Store Atmosphere on Customer Loyalty for Fore Coffee G-Walk Citraland Surabaya - Shafira Salsabilla; Supriyono Supriyono (Universitas KH. Abdul Chalim Mojokerto, 2025)
In the current era, the development of coffee shops is taking place very rapidly, so companies are required to innovate so that their products are superior to other competitors, following market desires. This research examines the influence of experiential marketing and store atmosphere on customer loyalty. This research is quantitative, using non-probability sampling and purposive sampling techniques in sampling. The population studied was customers of Fore Coffee G-Walk Citraland Surabaya, with a total of 112 respondents. The data analysis technique used is partial least squares (PLS). The research results show that experiential marketing and store atmosphere positively and significantly influence customer loyalty.